Eleven‐month longitudinal study of antibodies in SARS‐CoV‐2 exposed and naïve primary health care workers upon COVID‐19 vaccination. Issue 4 (6th September 2022) - Dobaño, Carlota; Ramírez‐Morros, Anna; Alonso, Selena; Ruiz‐Olalla, Gemma; Rubio, Rocío; Vidal, Marta; Prados de la Torre, Esther; Jairoce, Chenjerai; Mitchell, Robert A.; Barrios, Diana; Jiménez, Alfons; Rodrigo Melero, Natalia; et al.
Abstract: We evaluated the kinetics of antibody responses to Two years into the COVID‐19 pandemic and 1 year after the start of vaccination rollout, the world faced a peak of cases associated with the highly contagious Omicron variant of concern (VoC) of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike (S) and nucleocapsid (N) antigens over five cross‐sectional visits (January–November 2021), and the determinants of pre‐booster immunoglobulin levels, in a prospective cohort of vaccinated primary health care workers in Catalonia, Spain. Antibodies against S antigens after a full primary vaccination course, mostly with BNT162b2, decreased steadily over time and were higher in pre‐exposed ( n = 247) than naïve ( n = 200) individuals, but seropositivity was maintained at 100% (100% IgG, 95.5% IgA, 30.6% IgM) up to 319 days after the first dose. Antibody binding to variants of concern was highly maintained for IgG compared to wild type but significantly reduced for IgA and IgM, particularly for Beta and Gamma. Factors significantly associated with longer‐term antibodies included age, sex, occupation, smoking, adverse reaction to vaccination, levels of pre‐vaccination SARS‐CoV‐2 antibodies, interval between disease onset and vaccination, hospitalization, oxygen supply, post COVID and symptomatology. Earlier morning vaccination hours were associated with higher IgG responses in pre‐exposed participants. Symptomatic breakthroughs occurred in 9/447 (2.01%) individuals, all among naïve (9/200, 4.5%) and generally boosted antibody responses. Additionally, an increase in IgA and/or IgM seropositivity to variants, and N seroconversion at later time points (6.54%), indicated asymptomatic breakthrough infections, even among pre‐exposed. Seropositivity remained highly stable over almost a year after vaccination. However, gradually waning of anti‐S IgGs that correlate with neutralizing activity, coupled to evidence of an increase in breakthrough infections during the Delta and Omicron predominance, provides a rationale for booster immunization. Abstract : Antibodies against SARS‐CoV‐2 spike antigens after a primary vaccination course, mostly with BNT162b2, decreased steadily over five cross‐sectional visits (January–November 2021), being higher in pre‐exposed ( n = 247) than naïve ( n = 200) primary health care workers in Catalonia, Spain, but seropositivity was maintained at 100% up to 319 days after the first dose. Factors significantly associated with longer‐term antibodies included age, sex, occupation, smoking, adverse reaction to vaccination, levels of pre‐vaccination antibodies, hour of vaccination, interval between disease onset and vaccination, hospitalization, oxygen supply, post COVID and symptomatology. Antibody binding to variants of concern was highly maintained for IgG compared to wild type but significantly reduced for IgA and IgM, and symptomatic breakthroughs occurred in 2% individuals, all among naïve, and generally boosted antibody responses.